Nepotpune rečenice u književnoumjetničkom tekstu - Jovović, Nataša (Slavia Centralis, 2020)
INCOMPLETE SENTENCES IN A LITERARY TEXT This work analyses one of the expressive syntax processes – incomplete sentences at the example of a literary text. Our research corpus is comprised of novelistic works (The Wedding, Separation, The Wailing Mountain, Tide of War and Tamara) by one of the most significant South Slavic writers in the second half of the 20th century – Mihailo Lalić. His works were adapted for radio, television, film and theatre performances and they were translated into Russian, French, German, English, Ukranian, Danish, Czech, Slovakian, Romanian, Albanian, Turkish, Hungarian, Slovenian, Macedonian, Polish, Armenian, Lithuanian, Bulgarian and other languages. Considering the usage and presence of elliptical sentences in the examined text, the author answers the question, through syntactic, semantic and stylistic analyses, to what extent these sentences contribute to the stylistic constructions that enrich the linguistic expression of Mihailo Lalić and contribute to his originality
Keywords: incomplete sentences; literary text; Mihailo Lalić; syntactic; semantic and stylistic analyses; style